Impact of road traffic noise on obesity measures: observational study of three European cohorts - Cai, Y; Zijlema, WL; Sørgjerd, EP; Doiron, D; de Hoogh, K; Hodgson, S; Wolffenbuttel, B; Gulliver, J; Hansell, AL; Nieuwenhuijsen, M; Rahimi, K; Kvaløy, K (Elsevier, 2020)
Background: Environmental stressors such as transport noise may contribute to development of obesity through increased levels of stress hormones, sleep deprivation and endocrine disruption. Epidemiological evidence supporting an association of road traffic noise with obesity markers is still relatively scant and confined to certain geographical regions. We aimed to examine the cross-sectional associations between road traffic noise and obesity markers in three large European cohorts involving nearly 500,000 individuals.